(untitled) (Journal of Science and Technology, 2016)
Graphing Calculator Technology possesses a lot of capabilities in solving a variety of scientific and non-scientific problems. Its programming abilities make it very flexible to use. Unfortunately, it has been underutilised. In this paper, we develop an application with the graphing calculator to handle the processes in a Matching Scheme for Assigning Fish Types to Ponds. The application gives an inclusion matrix which is used as the basis of the matching and finally gives summary of the assignment..